Self-Efficacy and Speaking Proficiency Development through Communicative Language Teaching: A Case Study of College Students - Arum Putri Rahayu; Hendra Sudarso; Ahmad Fathir Imran; Azhariah Rachman; Himaya Praptani Adys (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study examined how speaking self-efficacy and speaking proficiency developed through Communicative Language Teaching (CLT) in an undergraduate EFL classroom at STAI Ma’arif Magetan, Indonesia. A qualitative case study design was employed. Data were collected from repeated classroom observations across an eight-session CLT unit, semi-structured interviews with twelve students, instructional documents, and students’ speaking task recordings rated descriptively with an analytic speaking rubric. Observational evidence showed increasing student talk time, frequent pair and group interaction, and growing negotiation of meaning as tasks progressed from information-gap exchanges to problem-solving discussions and short presentations with Q&A. Thematic analysis revealed five pathways of self-efficacy growth: mastery experiences from successful task completion, peer support, supportive feedback, systematic scaffolding, and emerging self-regulation strategies. Performance evidence from recordings indicated noticeable improvement in fluency and interactive communication, alongside gradual gains in intelligibility and vocabulary range, while grammatical accuracy improved more modestly. Triangulation across interviews, observations, and performance samples suggested a positive cycle in which higher self-efficacy increased willingness to speak and persistence, thereby expanding practice opportunities and strengthening proficiency. The study concludes that CLT, when implemented as a coherent system of progressive tasks, scaffolding, and constructive feedback, can effectively support confidence-building and speaking development in higher-education EFL settings. Pedagogically, instructors are encouraged to sequence tasks from low-stakes interaction to higher-stakes performance, provide language support, and use feedback that prioritizes intelligibility and next steps. Limitations include a single-site case and a short observation window; future studies may compare multiple classes and track longer-term retention of gains.